2013
DOI: 10.2486/indhealth.2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

Low Self-efficacy Is a Risk Factor for Depression among Male Japanese Workers: A Cohort Study

Abstract: The identification of risk factors for depression is necessary for the primary prevention of depression. The aim of this study is to determine whether self-efficacy (SE) is associated with onset of depression among workers. Medical expenditure records of 1,803 workers, who were clerks, system engineers, researchers, and service and sales workers in a software development company, were analyzed. Gender, age, job post, marital status, working hours, and SE were measured at baseline. Participants were divided acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…However, the associations between low CE and any as well as specific anxiety disorder(s) were no longer significant when adjusting for any other baseline disorder. These results correspond to and considerably extend previous research findings (Ehrenberg et al 1991;Baldwin et al 1993;Lee & Oei, 1993;Bandura et al 1999, Bögels & Zigterman, 2000Maciejewski et al 2000;Oei & Burrow, 2000;Hasking & Oei, 2002;Muris, 2002;Caprara et al 2006;Young et al 2006;Oei & Jardim 2007;Connor et al 2011;Sawatzky et al 2012;Taneichi et al 2013;Thorne et al 2013), since few prior studies prospectively examined the role of low CE for the onset of various mental disorders, including anxiety, depression and substance use. The particularly strong association between low CE and incident depression might be explained by the possibility that individuals feeling unable to cope with several situations in life developed a sense of non-contingency, uncontrollability and helplessness and therefore became depressed (Abramson et al 1978).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the associations between low CE and any as well as specific anxiety disorder(s) were no longer significant when adjusting for any other baseline disorder. These results correspond to and considerably extend previous research findings (Ehrenberg et al 1991;Baldwin et al 1993;Lee & Oei, 1993;Bandura et al 1999, Bögels & Zigterman, 2000Maciejewski et al 2000;Oei & Burrow, 2000;Hasking & Oei, 2002;Muris, 2002;Caprara et al 2006;Young et al 2006;Oei & Jardim 2007;Connor et al 2011;Sawatzky et al 2012;Taneichi et al 2013;Thorne et al 2013), since few prior studies prospectively examined the role of low CE for the onset of various mental disorders, including anxiety, depression and substance use. The particularly strong association between low CE and incident depression might be explained by the possibility that individuals feeling unable to cope with several situations in life developed a sense of non-contingency, uncontrollability and helplessness and therefore became depressed (Abramson et al 1978).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, previous research suggests that low levels of perceived coping efficacy (CE) might elevate the risk of developing psychopathology, including anxiety, depressive and substance use disorders (Ehrenberg et al 1991;Baldwin et al 1993;Lee & Oei, 1993;Bandura et al 1999;Bögels & Zigterman, 2000;Maciejewski et al 2000;Oei & Burrow, 2000;Hasking & Oei, 2002;Muris, 2002;Caprara et al 2006;Young et al 2006;Oei & Jardim, 2007;Connor et al 2011;Sawatzky et al 2012;Taneichi et al 2013;Thorne et al 2013). CE refers to a person's subjective sense that he/she will be able to cope effectively with difficulties in different areas of life and is conceptually closely related to constructs such as self-efficacy, optimism, perceived competences and problem-solving ability (Schwarzer, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This relationship between self-efficacy and depressive symptoms has been widely discussed in workers of different genders and different countries. 44,45 A high sense of self-efficacy can reduce the depressive symptoms of workers. One reason for this result may be that those with higher self-efficacy have more confidence, so they have better well-being and feel more like they belong.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy is defined as people’s beliefs about their capabilities to produce designated levels of performance that exercise influence over events that affect their lives [ 15 , 16 ]. Some studies have demonstrated associations between self-stigma and low self-esteem and self-efficacy [ 11 , 12 ], and others showed that levels of self-esteem and self-efficacy were related to the prevalence of depression [ 17 , 18 ]. We constructed a model whereby we hypothesized that “perception of radiation risk” influenced reproductive confidence (i.e., being able to deliver a baby safely), reproductive confidence influenced self-esteem and self-efficacy, and self-esteem and self-efficacy influenced depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%